Molecular motor-driven filament transport across three-dimensional, polymeric micro-junctions. (2nd December 2021) - Reuther, Cordula; Steenhusen, Sönke; Meinecke, Christoph Robert; Surendiran, Pradheebha; Salhotra, Aseem; Lindberg, Frida W; Månsson, Alf; Linke, Heiner; Diez, Stefan
Abstract: Molecular motor-driven filament systems have been extensively explored for biomedical and nanotechnological applications such as lab-on-chip molecular detection or network-based biocomputation. In these applications, filament transport conventionally occurs in two dimensions (2D), often guided along open, topographically and/or chemically structured channels which are coated by molecular motors. However, at crossing points of different channels the filament direction is less well determined and, though crucial to many applications, reliable guiding across the junction can often not be guaranteed. We here present a three-dimensional (3D) approach that eliminates the possibility for filaments to take wrong turns at junctions by spatially separating the channels crossing each other. Specifically, 3D junctions with tunnels and overpasses were manufactured on glass substrates by two-photon polymerization, a 3D fabrication technology where a tightly focused, femtosecond-pulsed laser is scanned in a layer-to-layer fashion across a photo-polymerizable inorganic–organic hybrid polymer (ORMOCER ® ) with µm resolution. Solidification of the polymer was confined to the focal volume, enabling the manufacturing of arbitrary 3D microstructures according to computer-aided design data. Successful realization of the 3D junction design was verified by optical and electron microscopy. Most importantly, we demonstrated the reliable transport of filaments, namely microtubules propelled by kinesin-1 motors, across these 3D junctions without junction errors. Our results open up new possibilities for 3D functional elements in biomolecular transport systems, in particular their implementation in biocomputational networks.